IMPLEMENTASI STRATEGI PEMBELAJARAN PAI BERBASIS NILAI DALAM MEMBANGUN NASIONALISME PESERTA DIDIK DI SMKN 1 MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR - Agus Triyana; Khoirul Anwar; Toha Makhshun (Indonesian Journal of Islamic Studies (IJIS), 2026)
This study aims to describe the implementation of value-based Islamic Religious Education (PAI) learning strategies in building student nationalism at SMKN 1 Modayag, East Bolaang Mongondow Regency, identify supporting and inhibiting factors, and analyze their impact on students' nationalistic attitudes and behavior. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that value-based PAI learning is implemented through the planning, implementation, and evaluation stages. Teachers integrate the values ​​of faith, morals, worship, honesty, responsibility, tolerance, cooperation, social concern, and love of the homeland in the learning process. The strategies used include storytelling, discussions, history learning, religious activities, social activities, and student involvement in school activities such as ceremonies, Scouts, and Paskibraka. Supporting factors include the principal's commitment, teacher quality, curriculum, facilities and infrastructure, the school environment, and parental and community support. Obstacles include low student motivation, limited time, lack of participation, and limited learning methods. The implementation of this strategy has a positive impact on increasing love for the homeland, tolerance, discipline, honesty, cooperation, and responsibility among students.